Lira Money Game for Strengthening Students’ Procedure Text Writing Skills: Permainan Uang Lira untuk Meningkatkan Keterampilan Menulis Teks Prosedur Siswa - Wulan, Afri Liyana Estri Sari; Rochmiyati, Siti (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Writing procedural texts remains a challenge for elementary students, particularly in organizing steps, using effective language, and maintaining coherence. Specific Background: Integrating local wisdom through ethnopedagogical, game-based learning is viewed as a promising approach to enhance contextual and engaging writing experiences. Knowledge Gap: However, limited research has explored how local culture–based educational games combined with the Tri-N approach (Niteni, Nirokke, Nambahi) can improve procedural writing skills in elementary school contexts. Aims: This study investigates the effectiveness of the “Uang Lira” (Ular Tangga Literasi dan Kearifan Lokal) game in improving Grade V students’ procedural text writing skills. Results: Using a qualitative descriptive design involving observation, interviews, and document analysis, the findings show notable improvement, with students’ average writing scores rising from 68.5 to 85.3. Students demonstrated better procedural structuring, clearer language use, and enriched cultural integration within their texts. Novelty: The study offers a culturally grounded game-based writing model that operationalizes the Tri-N framework to simultaneously develop literacy and cultural appreciation. Implications: These results suggest that culturally integrated educational games can serve as effective, contextually meaningful tools for enhancing procedural writing skills while fostering students’ connection to local traditions. Highlights: Highlights the effectiveness of the “Uang Lira” game in improving students’ procedural writing skills. Emphasizes the role of the Tri-N approach in strengthening observation, imitation, and development stages. Shows how integrating local culture enhances student engagement and contextual learning. Keywords: Procedure Text, Ethnopedagogy, Tri-n Approach, Educational Game, Writing Skills